Formation of communicative-ethnopedaogical competence of future teachers in the multiethnic environment of a modern university - Temirgalinova, Assel (Journal of International Students, 2026)
This study aimed to investigate the impact of ethnopedagogical teaching methods on the development of intercultural competencies among students of pedagogical faculties. The sample consisted of 298 first- and second-year students from the pedagogical faculties of polyethnic universities in Kazakhstan. An ethnopedagogical method-based teaching program was conducted for the experimental group, while the control group followed traditional teaching methods. The results indicated that in the experimental group, the frequency of interaction with representatives of language minorities increased, confidence in communication rose, and the difficulty in understanding foreign speech decreased. Thus, the study confirmed the effectiveness of ethnopedagogical methods in enhancing ethnopedagogical skills. The findings can be used in the development of educational programs for training teachers to work in multicultural educational institutions. The implementation of ethnopedagogical approaches contributes to the formation of tolerance, flexibility, and readiness for intercultural interaction among future educators, which is especially relevant in contemporary multilingual education.